(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Globalization and rapid technological advancements have redefined the educational landscape, demanding new approaches to teaching and learning. Information and Communication Technology (ICT) has emerged as a vital driver of educational reform, offering transformative tools that enhance accessibility, quality, and student engagement. This study investigates the impact of ICT in higher education through a mixed-methods approach, utilizing data from 300 stakeholders including students and educators. The findings reveal a strong consensus on the positive role of ICT in improving comprehension of complex topics, instructional delivery, and digital learning experiences. However, challenges such as poor infrastructure, lack of digital skills, and limited institutional support persist, especially in rural and government institutions. The study concludes with actionable insights for policy formulation and institutional strategy aimed at optimizing ICT integration in the education sector.